# How to find points of intersection of a parabola and an exponential w/o graphing?

• Apr 12th 2013, 12:34 PM
moskowfreak1111
How to find points of intersection of a parabola and an exponential w/o graphing?
Hey mathhelpforum.com, this is my first post! And I need some help with math!

The equation is 3^x+5=x^2-5, we aren't supposed to be able to solve them yet non-graphically, so I wonder if it is even possible, if so, how?
• Apr 12th 2013, 04:34 PM
HallsofIvy
Re: How to find points of intersection of a parabola and an exponential w/o graphing?
There is no simple "algebraic" method. You say you aren't supposed to solve it "graphically". Is some other numerical method allowed?
• Apr 12th 2013, 06:53 PM
moskowfreak1111
Re: How to find points of intersection of a parabola and an exponential w/o graphing?
Well, we can, and that's the only way to solve it is graphically my teacher says, but I don't want to, I want to actually learn how to do it, what would be the non-simple ways to do it?
• May 15th 2013, 01:42 PM
x3bnm
Re: How to find points of intersection of a parabola and an exponential w/o graphing?
Quote:

The equation is 3^x+5=x^2-5, we aren't supposed to be able to solve them yet non-graphically, so I wonder if it is even possible, if so, how?
For Nonlinear equations like yours you can use secant method.

Explanation of Secant Method:

Suppose there's a nonlinear function $y = f(x)$ in the image given below:

Attachment 28376

(a) Now take any two values of $x$ along the $X$ axis Say the first one is $p_0$ and the second one is $p_1$

(b) plug the value of $p_0$ and $p_1$ into $y = f(x)$ and solve for $y$.

(c) You will get two points. They are $(p_0, f(p_0))$ and $(p_1, f(p_1))$

(d) draw a secant line that goes through $(p_0, f(p_0))$ and $(p_1, f(p_1))$

That secant line is $L1$

$L1$ intersects $X$ axis at $p_2$

(e) If you look carefully we can now write:

$\frac{f(p_1)}{p_1 - p_2} = \frac{f(p_1)-f(p_0)}{p_1 - p_0}......[\text{Equation (1)}]$

(f) Plug the values of $p_0$, $f(p_0)$, $p_1$ and $f(p_1)$ and you will get the value $p_2$

(g) Now plug the value of $p_2$ into $y = f(x)$ as the value of $x$ and solve for $y$

you'll get the point $(p_2, f(p_2))$

(h) A secant line can be drawn from $(p_1, f(p_1))$ to the point $(p_2, f(p_2))$ which is $L2$.

$L2$ intersects $X$ axis at $p_3$

(i) Again we can write:

$\frac{f(p_2)}{p_2 - p_3} = \frac{f(p_2)-f(p_1)}{p_2 - p_1}$

Now plug in $p_1$, $f(p_1)$, $p_2$ and $f(p_2)$ and solve for $p_3$

(j) Again plug this value of $x = p_3$ into $y =f(x)$ and find $f(p_3)$

(k) Now continue this process iteratively until a value of $x$ is reached that will make $y = f(x)$ closer to zero.
And that's it that's the root of the equation.

We can write Equation(1) as:

$\frac{f(p_{n-1})}{p_{n-1} - p_n} = \frac{f(p_{n-1})-f(p_{n-2})}{p_{n-1} - p_{n-2}}......[\text{Equation (2)}]$

You want to find the root of the equation is:

$3^x - x^2 + 10 = 0$

So the function is:

$f(x) = 3^x - x^2 + 10.......(3)$

(1) Take any two $x$ values along the $X$ axis. Say the first point $p_{n-2} = 2$ and $p_{n-1} = 3$

$f(p_{n-2}) = f(2) = 15.....\text{[by plugging in } x = 2 \text{into function labeled as (3)]}$

And:

$f(p_{n-1}) = f(3) = 28$

(2) Now plug in $p_{n-1}, f(p_{n-1}), p_{n-2}, f(p_{n-2})$ into Equation(2) and solve for $p_{n}$

You'll get $p_n = 0.84615$

(3) Now let $p_{n-2} = p_{n-1} = 3$ and $p_{n-1} = p_n = 0.84615$

And do step (1) to (3) then again and again until plugging in the new found $p_n$ in each step as value of $x$ into $y = 3^x - x^2 + 10$ gets reasonably closer to zero.

After 10 iterations I got the root of $y = 3^x - x^2 + 10$. And it's $x = -3.16715$

If I plug this value in $y = 3^x - x^2 + 10$ I get $-0.00002$ which is reasonably close.

So the approximate answer is: $x = -3.16715$

 pn-1 pn-2 f(pn-1) f(pn-2) pn 3 2 28 15 0.84615 0.84615 3 11.81750 28 -0.72673 -0.72673 0.84615 9.92191 11.81750 -8.95951 -8.95951 -0.72673 -70.27277 9.92191 -1.74531 -1.74531 -8.95951 7.10088 -70.27277 -2.40739 -2.40739 -1.74531 4.27549 7.10088 -3.40928 -3.40928 -2.40739 -1.59957 4.27559 -3.13651 -3.13651 -3.40928 0.19418 -1.59957 -3.16604 -3.16604 -3.13651 0.00705 0.19418 -3.16715 -3.16715 -3.16604 -0.00002 0.00705 -3.16715